2002
DOI: 10.1038/nm727
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of gastric inhibitory polypeptide signaling prevents obesity

Abstract: Secretion of gastric inhibitory polypeptide (GIP), a duodenal hormone, is primarily induced by absorption of ingested fat. Here we describe a novel pathway of obesity promotion via GIP. Wild-type mice fed a high-fat diet exhibited both hypersecretion of GIP and extreme visceral and subcutaneous fat deposition with insulin resistance. In contrast, mice lacking the GIP receptor (Gipr(-/-)) fed a high-fat diet were clearly protected from both the obesity and the insulin resistance. Moreover, double-homozygous mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

56
688
3
16

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 829 publications
(779 citation statements)
references
References 21 publications
56
688
3
16
Order By: Relevance
“…Seminal studies performed by Han et al [11] demonstrated that WB increases the expression of proteins related to fatty acid oxidation by modulating the sterol-regulatory element binding protein pathway, and increases lipolysis and browning of adipocytes [12] in mice. On the other hand, many studies have demonstrated that chronic disruption and suppression of GIP signaling, either genetically, or by vaccination against GIP, or by administration of materials that reduce postprandial blood GIP, leads to high fat utilization and accelerates lipolysis in adipose tissue [2125,2729,34]. The findings of the present study are consistent with previous findings, and add new insight into the anti-obesity mechanisms of WB.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Seminal studies performed by Han et al [11] demonstrated that WB increases the expression of proteins related to fatty acid oxidation by modulating the sterol-regulatory element binding protein pathway, and increases lipolysis and browning of adipocytes [12] in mice. On the other hand, many studies have demonstrated that chronic disruption and suppression of GIP signaling, either genetically, or by vaccination against GIP, or by administration of materials that reduce postprandial blood GIP, leads to high fat utilization and accelerates lipolysis in adipose tissue [2125,2729,34]. The findings of the present study are consistent with previous findings, and add new insight into the anti-obesity mechanisms of WB.…”
Section: Discussionsupporting
confidence: 92%
“…GIP has various anabolic effects via GIPRs on adipocytes, including stimulation of glucose uptake, lipoprotein lipase activity [18,19], and fatty acid synthesis [20]. Genetically GIPR-ablated mice exhibit high fat utilization and resistance to high-fat induced obesity [21,22]. In addition, daily injection of a specific GIPR antagonist protects mice against obesity [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, plasma GIP concentrations have been reported to be elevated in obesity-related type 2 diabetes [28] and animals with obesity-related diabetes [29]. Experimental evidence in mice also indicates that inhibition of GIP signalling by genetic knockout of the GIP receptor prevents diet-induced obesity through the preferential use of fat as an energy substrate [30]. Furthermore, it has been shown that short-term administration of the specific and stable GIP receptor antagonist (Pro 3 )GIP [31] can reverse many of the established metabolic abnormalities in adult ob/ob mice [32].…”
Section: Introductionmentioning
confidence: 62%
“…3 When fed a high-fat diet, GIP receptor-deficient mice (GIPR -/-) maintained normal weight, while the body weight of wild-type littermates increased by 35%. Furthermore, subcutaneous and visceral fat mass, as well as the size of the adipocytes isolated from epididymal fat pads, were significantly enhanced in GIPR +/+ mice when compared to GIPR -/-mice.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, subcutaneous and visceral fat mass, as well as the size of the adipocytes isolated from epididymal fat pads, were significantly enhanced in GIPR +/+ mice when compared to GIPR -/-mice. 3 In addition, Clements et al have reported that patients who undergo Roux-en-Y gastric bypass surgery (RYGB), which bypasses portions of small intestine that produce and secrete GIP, not only lose weight, but also significantly improve their glucose tolerance. 4 Moreover, they found that fasting plasma concentrations of GIP, insulin, and C-peptide all steadily declined following the surgery, starting before significant weight loss was evident.…”
Section: Introductionmentioning
confidence: 99%